PENGARUH EKSTRAK PROPOLIS Trigona Sp DENGAN BERBAGAI KONSENTRASI DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Streptococcus alpha ISOLAT PLAK GIGI ANAK (KAJIAN IN VITRO) - , HERI ISWANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Streptococcus alpha bacteria is the most dominant bacteria and plays an important role in the early formation of dental plaque. Streptococcus alpha bacteria growth can be inhibited by natural antibacterial ingredients such as Trigona sp propolis extract containing flavonoids. The purpose of this study was to determine the effect of Trigona sp propolis extract in inhibiting the growth of Streptococcus alpha bacteria isolated from dental plaque of children. In vitro studies conducted on Trigona sp propolis extract concentration of 4%, 6%, 8% and 10% obtaine from the maceration of honeycomb Ambarawa- Trigona Sp of Central Java with 70% ethanol. Streptococcus alpha bacteria isolates obtained from dental plaque of pediatric patients in pediatric dentistry clinic of Prof Soedomo dental hospital. Streptococcus alpha bacteria growth inhibition zone was observed with diffusion method. Replication of three times for each concentration. Data were analized with the Kruskal-Wallis and Man-Witney test. The results showed there were significant differences in the average growth inhibition zone of Streptococcus alpha (p <0.05)between Trigona sp propolis extract concentration of 4%, 6%, 8% and 10%. By increasing the concentration of Trigona sp propolis extract occurs every 2% increase in inhibition zone between 0.38 to 0.57 mm. There are significant differences in the average inhibition zone between each concentration of Trigona sp propolis extract (p â¤ 0.05). It was concluded that the concentration of 4% to 10% Trigona Sp propolis extact increased the average inhibition zone of Streptococcus alpha bacteria growth of childrenâs dental plaque. Keywords : Trigona Sp propolis extract, Streptococcus alpha bacteria, dental plaque of children, growth inhibition zone